2005
DOI: 10.1385/ncc:2:3:263
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recombinant Factor VIIa in Patients With Warfarin-Associated Intracranial Hemorrhage

Abstract: Introduction-Warfarin-associated intracranial hemorrhage (ICH) requires rapid normalization of clotting function. Current therapies are associated with significant complications and/or prolonged time to correction of coagulopathy. Recombinant factor VIIa (FVIIa) might allow faster and safer correction of coagulopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 18 publications
1
81
0
5
Order By: Relevance
“…74,75 Early reports of the off-label use of rFVIIa from one of our institutions as well as others on the successful management of warfarinassociated ICH with rFVIIa therapy led to the development of single-institution policies for oversight of its off-label use. [76][77][78][79][80] The value of rFVIIa in patients with spontaneous ICH who were not on warfarin anticoagulation underwent scrutiny in clinical trials in which it was shown to reduce growth of hematoma if administered within 4 hours of onset, 81 but it did not improve survival or functional outcome. 82 A subsequent post hoc analysis of these trials suggested that the use of rFVIIa was most beneficial and associated with improved outcomes in patients Յ 70 years old who had lower baseline hemorrhage volume and shorter time from onset to treatment.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
See 1 more Smart Citation
“…74,75 Early reports of the off-label use of rFVIIa from one of our institutions as well as others on the successful management of warfarinassociated ICH with rFVIIa therapy led to the development of single-institution policies for oversight of its off-label use. [76][77][78][79][80] The value of rFVIIa in patients with spontaneous ICH who were not on warfarin anticoagulation underwent scrutiny in clinical trials in which it was shown to reduce growth of hematoma if administered within 4 hours of onset, 81 but it did not improve survival or functional outcome. 82 A subsequent post hoc analysis of these trials suggested that the use of rFVIIa was most beneficial and associated with improved outcomes in patients Յ 70 years old who had lower baseline hemorrhage volume and shorter time from onset to treatment.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…Finally, 2 case series of patients with ICH who received rFVIIa for normalization of INR also had subgroups of patients who underwent neurosurgical procedures with adequate hemostasis. 76,97 Recently, Nishijima et al 98 studied 40 patients receiving warfarin who were admitted to the ED for traumatic ICH and reported that administration of rFVIIA was associated with shorter time to normal INR; however, there was no difference in mortality (or in thromboembolic complications) among patients who received rFVIIA and patients who did not.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…30 -32 A recent review of 12 patients with acute warfarinassociated ICH over this same time period at one institution, all of whom received rFVIIa (30 -135 g/kg) as well as vitamin K (10 mg/day for 3 days) and fresh-frozen plasma (1307 Ϯ 652 mL) for treatment, found that treatment was associated with rapid correction of INR, and that single doses appeared safe in this high-risk population. 32 These observations indicate that rFVIIa may be used to reverse the effect of warfarin or other vitamin K-antagonist therapy in cases in which the administration of vitamin K alone has been found to be insufficient. In contrast, the risk of TAEs observed in clinical trials evaluating off-label uses of rFVIIa has raised concerns.…”
Section: Rfviia Use In Spontaneous Ichmentioning
confidence: 99%
“…The ability of rFVIIa to effect hemostasis in other clinical settings has also been demonstrated in case reports and clinical trials. [23][24][25][26] In a randomized, controlled trial investigating the safety and efficacy of rFVIIa in patients with upper gastrointestinal bleeding (UGIB) and cirrhosis, there was no significant effect of rFVIIa treatment on the number of 5-day failures in the total population. 8 However, a finding from posthoc analysis was that rFVIIa significantly reduced the number of 5-day failures and improved 24-hour bleeding control in the subgroup of Child-Pugh B and C patients with variceal bleeding, which were the patients with greater impairment of hemostatic parameters.…”
mentioning
confidence: 99%